Flight dispersion in field and reproductive status of Scaptocoris castanea Perty (Hemiptera: Cydnidae) - Souza, Camila Patrícia Ribeiro; Turchen, Leonardo Morais; Cossolin, Jamile Fernanda Silva; Pereira, Mônica Josene Barbosa (EntomoBrasilis, 2019)
Abstract. Flight dispersion is an adaptive trait to insects, since that make possible found new habitat with resources adequate to survive and reproduction. This behavior is reported in Scaptocoris castanea Perty (Hemiptera: Cydnidae), however few is known on this issue. Herein, we propose to characterize the flight dispersion of S. castanea in field and assess your reproductive status. For this, we conducted samples in soybean and cotton crop by two years (i.e. crop station), where the insects were collected with aerial insect net and sample in soil. We assess presence and/or absence of insect at flight dispersion, sexual rate and reproductive status of females (flight and soil), which was defined as presence of sperm in the spermatheca (i.e. couple female) and number of ovules in ovaries (i.e., full eggs). Our results exhibit that dispersion by flight occurred between March and April (2014) and, February and March (2015), which indicate strong association among flight dispersion and rain period. Besides, we verified that the insects collected during flight exhibit a high proportion of female (> 0.85), and high reproductive potential from insect at flight and in soil. Therefore, the flight dispersion in S. castanea is characterized by occur after mating behavior (presence of sperm in spermatid) and with insect able to colonize new fields (presence of ovules in ovaries). Dispersão por voo em campo e status reprodutivo de Scaptocoris castanea Perty (Hemiptera: Cydnidae) Resumo. Dispersão por voo é uma característica adaptativa em insetos, pois permitem a localização de habitat favoráveis para sobrevivência e reprodução. Tal comportamento é realizado pelo percevejo-castanho, Scaptocoris castanea Perty (Hemiptera: Cydnidae), mas pouca atenção tem sido dada a esta questão. Assim, propõe-se nesta pesquisa caracterizar a dispersão por revoada e status reprodutivo de S. castanea em campo. Para isso, realizou-se coletas em áreas de soja e algodão em dois anos (safras). Estas consistiam em captura de insetos em revoadas com rede entomológica e coletas em solo. Avaliou-se a razão sexual dos adultos e o status reprodutivo das fêmeas (revoada e solo), considerando a presença de espermatozoides na espermateca e fêmeas com óvulos nos ovaríolos (óvulos formados). Nossos resultados mostraram que a dispersão por voo ocorreu entre março e abril (2014) e fevereiro e março (2015), o que indica forte associação da dispersão com período da chuva. Além disso, verificou-se que os insetos coletados durante o voo exibiam alta proporção de fêmeas (> 0,85) e alto potencial reprodutivo de fêmeas em voo e no solo. Portanto, pode-se concluir que a dispersão de S. castanea é caracterizada por ocorrer após comportamento de cópula (presença de esperma na espermateca) e com insetos aptos para colonizar novas áreas (presença de óvulos nos ovaríolos).